Information System Application Alanysis And Design Web-Based Network Complaints Using Php And Bootsrap On Diskominfo - Wilda, Wilda Maudyna; Hanum, Latifah (Ali Institute or Research and Publication, 2022)
Network complaints services at the Tebing Tinggi City Communications and Information Office are handled by IT Support, complaints reports regarding network or device problems are received by telephone or Service employees come directly to the office with hardware included. IT Support uses Microsoft Word as an application to input report data regarding network complaints, this system is considered ineffective and can cause errors during input. This study aims to design and build a web-based network complaint application using the codeigniter and bootsrap framework. As for designing this website system, the researcher uses programming, namely MySQL as the database and PHP as the programming language, while the system development method uses Waterfall. The results of this study are a website-based network complaint application which is expected to provide a solution so that service and data processing of network complaints can be handled more quickly.